ANALISIS EFEKTIFTAS BIAYA TERAPI ANTIKOAGULAN UNTUK PROFLAKSIS TROMBOSIS VENA PASCA TOTAL HIP AND KNEE REPLACEMENT - Luthfiyanti, Niken; Pratama, Kharisma Jayak; Safitri, Ayu Dwi; Noviana (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Orthopedic surgery such as surgery on the hip and knee have a high risk of experiencing Deep Vein Tromoembolism (DVT), especially in patients with hypercoagulability. In patients undergoing Hip and Knee Replacement, one of the standard therapies for treating DVT is by administering combination therapy (Unfractionated Heparin + Warfarin). Rivaroxaban is another therapy for the treatment of DVT which is a new oral anticoagulant (NOAC), which was developed to address the limitations of previous standard therapy, but has a more expensive price per unit. Pharmacoeconomic studies are carried out to determine the cost-effectiveness of patient treatment, one of which is carried out Cost Effectiveness Analysis (CEA), used in making decisions about selecting the best alternative in selecting medical costs. This study aims to analyze the most effective anticoagulant prophylaxis in post-treatment patients Hip and Knee Replacement at Dr. Regional General Hospital. Moewardi Surakarta. Observational descriptive research with retrospective data collection and using the CEA method. The data taken is in the form of medical records of patients undergoing procedures Total Hip and Knee Replacement with prophylactic therapy with anticoagulants. Samples were taken from 50 patients who met the inclusion and exclusion criteria. The research results showed that the ACER value of patients who used rivaroxaban prophylaxis cost Rp 24.569/day and patients who use LMWH prophylaxis incur a cost of Rp 36.304/day, so it can be concluded that the use of the drug rivaroxaban is more cost effective at RSUD Dr. Moewardi Surakarta.